Dual analysis of postural control in middle-aged and elderly patients with cervicogenic dizziness: Dynamic and static balance perspectives - Luo, Wei; Min, Yu; Chen, Peishun; Li, Hao; Long, Zhiyong; Sun, Ju; Zhong, Tao (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectivesThis study aimed to comprehensively analyze the postural control characteristics of middle-aged and elderly patients with cervicogenic dizziness from both dynamic and static balance perspectives.MethodsA cross-sectional study was conducted involving 20 patients with cervicogenic dizziness (dizziness group) and 20 healthy individuals (health group). Using the Prokin Balance Instrument, we conducted static balance and limits of stability tests on both groups. Key metrics such as average speed of sway, standard deviation of sway, average center of pressure, Romberg’s ratio, and limits of stability values were recorded.ResultsWith the exception of the standard deviation of mediolateral sway in the healthy group, the values of static balance indices were higher in the eyes-closed condition compared to the eyes-open condition for both groups (|Z| > 2.068, P < 0.05). Except for the average speed of mediolateral sway in both the eyes-open and eyes-closed conditions and the length of body sway in the eyes-open condition, the remaining static balance index values were higher in the dizziness group than in the healthy group (|Z| > 2.077, P < 0.05). Compared to the healthy group, the Romberg ratio was significantly higher in the dizziness group, while the values of the limits of stability were significantly lower (P < 0.05). Furthermore, the average center of pressure along the X and Y-axes exhibited a dispersed distribution pattern away from the axis in the dizziness group, in contrast to the healthy group, which demonstrated a concentrated distribution pattern close to the axis.ConclusionMiddle-aged and elderly patients with cervicogenic dizziness demonstrate postural control abnormalities, including decreased static balance, reduced limits of stability, increased center of gravity sway, reliance on visual compensation for postural control, and an elevated risk of falls.